Karakteristik Kadar Abu Serbuk Gergaji Kayu Jati Setelah Pencucian Berdasarkan Analisis Proksimat - Muhammad Arief Saputro; Mochamad Syamsiro; Noesanto Dewantoro Ahmad; Bayu Megaprastio; Dimas Noor Ardianto (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
Teak sawdust biomass has potential as a solid fuel; however, its high ash and inorganic mineral contents adversely affect its fuel quality and thermal performance. Previous studies on biomass leaching generally evaluated process effectiveness solely based on mass loss after leaching, so the relationship between mass reduction and the actual decrease in ash content has not been fully verified. Therefore, this study emphasizes the verification of ash reduction through proximate analysis as a more representative indicator of biomass quality, while also evaluating its effect on improving calorific value. This study aimed to compare the effectiveness of leaching using deionized water and 1 M HCl in reducing ash content and increasing calorific value. The experiment was conducted using solid-to-liquid ratios of 1:25, 1:50, and 1:75, with 2 h of stirring, drying at 105 °C, followed by proximate and calorific value analyses. The results showed that leaching with 1 M HCl effectively reduced the ash content by 30%, from 2.013% in the raw biomass to 1.402%, whereas leaching with deionized water did not result in a significant reduction in ash content. In addition, the calorific value increased by 1.078 MJ/kg, from 17.629 MJ/kg in the raw biomass to 18.707 MJ/kg after leaching with 1 M HCl. Overall, 1 M HCl exhibited superior demineralization performance compared to deionized water. These findings indicate that acid leaching significantly improves fuel quality by reducing inorganic mineral content and increasing energy density.